Role of Islamic-Based Caring in Enhancing the Spiritual Well-Being of Critically Ill Patient: A Narrative Review - Dhea Praditiya; Suhartini Suhartini; Wahyu Hidayati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Critically ill patients in intensive care units (ICUs) frequently experience psychological stress, anxiety, and uncertainty, which can adversely affect recovery and overall quality of life. Spiritual well-being is a crucial dimension of holistic care, particularly for Muslim patients, as it promotes inner peace, resilience, and coping during critical illness. Islamic-based caring integrates religious practices, including prayer, dhikr, and Qur’an recitation, into nursing interventions to address patients’ spiritual needs. This narrative review aimed to examine the role of Islamic-based caring in enhancing spiritual well-being among critically ill patients, focusing on its psychological, physiological, and spiritual outcomes, and the contributions of nurses, families, and healthcare institutions in facilitating effective spiritual care. A literature search was conducted in Scopus, PubMed, ScienceDirect, and SINTA using keywords such as “Islamic-based caring,” “Qur’an recitation,” “critical care,” and “spiritual well-being.” Inclusion criteria encompassed peer-reviewed studies on adult ICU or critically ill patients published between 2015 and 2025, in English or Indonesian, and focusing on Islamic spiritual interventions. Excluded were pediatric populations and non-Islamic interventions. After screening 134 articles, 11 studies that met the inclusion criteria were finally analyzed and synthesized narratively. Islamic-based interventions, including Qur’an recitation, audio therapy, prayer facilitation, dhikr, and mindfulness programs, consistently reduced anxiety, depression, and pain while enhancing emotional stability and spiritual well-being. Several studies reported shorter ICU or hospital stays. Nurses were identified as primary facilitators, families provided emotional and spiritual support, and institutional policies and facilities influenced implementation. Islamic-based caring is a safe, cost-effective, and holistic approach that improves psychological, physiological, and spiritual outcomes in critically ill patients. Effective integration requires multi-level collaboration, formal training, supportive policies, and family involvement, reinforcing its potential as a standard component of critical care practice.